Potential targets and applications of nanodrug targeting myeloid cells in osteosarcoma for the enhancement of immunotherapy - Zhu, Jianshu; Fan, Jiawei; Xia, Yuanliang; Wang, Hengyi; Li, Yuehong; Feng, Zijia; Fu, Changfeng (Frontiers in Pharmacology, 2023)
Targeted immunotherapies have emerged as a transformative approach in cancer treatment, offering enhanced specificity to tumor cells, and minimizing damage to healthy tissues. The targeted treatment of the tumor immune system has become clinically applicable, demonstrating significant anti-tumor activity in both early and late-stage malignancies, subsequently enhancing long-term survival rates. The most frequent and significant targeted therapies for the tumor immune system are executed through the utilization of checkpoint inhibitor antibodies and chimeric antigen receptor T cell treatment. However, when using immunotherapeutic drugs or combined treatments for solid tumors like osteosarcoma, challenges arise due to limited efficacy or the induction of severe cytotoxicity. Utilizing nanoparticle drug delivery systems to target tumor-associated macrophages and bone marrow-derived suppressor cells is a promising and attractive immunotherapeutic approach. This is because these bone marrow cells often exert immunosuppressive effects in the tumor microenvironment, promoting tumor progression, metastasis, and the development of drug resistance.Moreover, given the propensity of myeloid cells to engulf nanoparticles and microparticles, they are logical therapeutic targets. Therefore, we have discussed the mechanisms of nanomedicine-based enhancement of immune therapy through targeting myeloid cells in osteosarcoma, and how the related therapeutic strategies well adapt to immunotherapy from perspectives such as promoting immunogenic cell death with nanoparticles, regulating the proportion of various cellular subgroups in tumor-associated macrophages, interaction with myeloid cell receptor ligands, activating Running Title 2 immunostimulatory signaling pathways, altering myeloid cell epigenetics, and modulating the intensity of immunostimulation. We also explored the clinical implementations of immunotherapy grounded on nanomedicine.